Musculoskeletal tissues-on-a-chip: role of natural polymers in reproducing tissue-specific microenvironments. (1st October 2022) - Petta, D; D'Amora, U; D'Arrigo, D; Tomasini, M; Candrian, C; Ambrosio, L; Moretti, M
Abstract: Over the past years, 3D in vitro models have been widely employed in the regenerative medicine field. Among them, organ-on-a-chip technology has the potential to elucidate cellular mechanism exploiting multichannel microfluidic devices to establish 3D co-culture systems that offer control over the cellular, physico-chemical and biochemical microenvironments. To deliver the most relevant cues to cells, it is of paramount importance to select the most appropriate matrix for mimicking the extracellular matrix of the native tissue. Natural polymers-based hydrogels are the elected candidates for reproducing tissue-specific microenvironments in musculoskeletal tissue-on-a-chip models owning to their interesting and peculiar physico-chemical, mechanical and biological properties. Despite these advantages, there is still a gap between the biomaterials complexity in conventional tissue engineering and the application of these biomaterials in 3D in vitro microfluidic models. In this review, the aim is to suggest the adoption of more suitable biomaterials, alternative crosslinking strategies and tissue engineered-inspired approaches in organ-on-a-chip to better mimic the complexity of physiological musculoskeletal tissues. Accordingly, after giving an overview of the musculoskeletal tissue compositions, the properties of the main natural polymers employed in microfluidic systems are investigated, together with the main musculoskeletal tissues-on-a-chip devices.